2017
DOI: 10.1534/genetics.117.300189
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionarily Conserved Alternative Splicing Across Monocots

Abstract: One difficulty when identifying alternative splicing (AS) events in plants is distinguishing functional AS from splicing noise. One way to add confidence to the validity of a splice isoform is to observe that it is conserved across evolutionarily related species. We use a high throughput method to identify junction-based conserved AS events from RNA-Seq data across nine plant species, including five grass monocots (maize, sorghum, rice, Brachpodium, and foxtail millet), plus two nongrass monocots (banana and A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 91 publications
2
19
0
Order By: Relevance
“…Alternative splicing is closely associated with many abiotic stresses (salt stress, drought, flooding, temperature, etc.) 56 and contributes to the evolution of phenotypic novelty 57 . We also detected genes related to DNA repair and recombination, including nucleotide excision repair and homologous recombination.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative splicing is closely associated with many abiotic stresses (salt stress, drought, flooding, temperature, etc.) 56 and contributes to the evolution of phenotypic novelty 57 . We also detected genes related to DNA repair and recombination, including nucleotide excision repair and homologous recombination.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative splicing (AS) can increase a complexity of transcriptome and proteome via generating multiple transcripts and protein isoforms from the single gene. Up to 95% of mammalian precursor messenger RNAs (pre-mRNAs) are alternatively spliced ( Pan et al, 2008 ) whereas recent studies in higher plants suggest that AS is fairly conserved ( Mei et al, 2017a ) and is observed in approximately 42–61% of intron-containing genes ( Filichkin et al, 2010 ; Marquez et al, 2012 ). Common types of AS include intron retention (IR), exon skipping (ES), the alternative donor (alt 5â€Č) or acceptor (alt 3â€Č) splice site, and mutually exclusive exons ( Figure 1A ).…”
Section: Introductionmentioning
confidence: 99%
“…A study of a drought-resistant rice breeding line found drought-specific splicing events as well as differences in the functions of genes undergoing AS (Wei et al, 2017 ). Evidence for evolutionary conservation of AS events across syntenous species suggests that the functions of AS in the stress responses of wheat and maize are likely to exist in rice as well (Mei et al, 2017a ).…”
Section: Introductionmentioning
confidence: 99%